Preparation and performance evaluation of biodegradable corn starch film using poly (lactic acid) as waterproof coating. (2nd June 2020) - Chang, Qinglu; Hao, Yanling; Cheng, Long; Liu, Yihao; Qu, Aoyun
ABSTRACT: The wide use of synthetic plastic causes serious environmental pollution. Starch is used as potential alternative for non-degradable petrochemical polymers to prepare biodegradable plastic. In this work the biodegradable corn starch films were prepared, using poly (lactic acid) (PLA) coating to improve its waterproof performance. Effects of different PLA concentration on the waterproof performance of corn starch films were evaluated. Compared to starch film without PLA coating, the films coated with PLA significantly reduces water solubility and increases the mechanical stability. The film coated with 6% w v −1 PLA exhibited an excellent reduction of 40.74% in moisture absorption and an increase of 46.6% in tensile strength compared to uncoated film.